Аspects of the formation of the religious identity of young people - Sailaubekkyzy, A. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2019)
One of the most important questions of the science of religion is the question of religious identity and various aspects of its manifestation. In modern conditions, the processes of religious identification turn out to be due to new civilizational factors leading to the dysfunction of traditional institutions of socialization and the formation of a new type of consciousness. This actualizes the need to produce an integrated approach to solving a number of important problems of religious studies, including the problems of religious identity. In a multicultural society, when there is a danger of losing the semantic universal foundations of universal culture, a young man has difficulty in choosing identification reference points. The traditional foundations of culture in a dynamically changing society are exposed to cultural patterns that reflect various systems of values and social norms associated with the loss of the metaphysical foundations of a person’s existence, goals of existence, and development values. Thе aim of the study is devoted to the consideration of religious identity and aspects of the formation of the religious identity of young people. The article examines such aspects of religious identity as the participation of educational programs in the formation of the religious identity of young people, the introduction of a new subject – “Secularism and the foundations of religious studies”. Also shown the results of a sociological study of teachers of the subject – “Secularism and the foundations of religious studies” Key words: religion, religious consciousness, religious identity, secularity